KEMAMPUAN KECUKUPAN ANGGARAN MEMODERASI PENGARUH PARTISIPASI ANGGARAN PADA SENJANGAN ANGGARAN - Liandini, Vazria Ulfa; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
This research aimed to get empirical evidence of the effect of budgetary participation on budgetary slack and moderating influence of the adequacy of the budget as budgetary participation influence on budgetary slack. The theory used in this research is the theory of the Agency (Agency Theory). The population in this study are managers and employees involved in the budgeting process at 126 construction companies in the city of Denpasar. Samples in this research that 39 construction companies in the city of Denpasar with purposive sampling method. The data collection by questionnaire. Data analysis technique used is a simple linear regression analysis and Moderated Regression Analysis (MRA). The results of this research showed that budgetary participation variable significant positive effect on budgetary slack. Variable of the adequacy of the budget weaken the influence of budgetary participation on budgetary slack.
Keywords: the adequacy of the budget, budgetary participation, budgetary slack